The orphan master's son [compact disc, unabridged] : a novel - Johnson, Adam, 1967- (Random House Audio, 2012)
The Orphan master's son follows a young man's journey through the icy waters, dark tunnels, and eerie spy chambers of the world's most mysterious dictatorship, North Korea.